Comunicación digital y su aplicación mediante la creación de contenidos multimedia para posicionar la marca en la red social facebook, de la empresa Riosanet en la ciudad de Guaranda en el periodo 2025. - Llivicota Tandapilco, Wilmer Alfredo (2025)
Digital communication has revolutionized the way brands connect with their communities, establishing social media as a key tool for fostering interaction and dialogue in modern society. In Guaranda, Ecuador, Riosanet, an internet service provider, leverages Facebook to share information about its plans and promotions while strengthening ties with the local community. Through dynamic and strategic multimedia content, the company aims to consolidate its market positioning in 2025, promoting trust and loyalty among citizens. This research examines how the creation and dissemination of multimedia content on social media enhances Riosanet’s visibility and contributes to building a strong local identity. It highlights the importance of tailoring content to the cultural and social preferences of the audience to maximize its impact on brand perception. The findings aim to propose strategies to optimize Riosanet’s digital presence and reinforce its role as a key player in the Guaranda community.